GERAKAN LITERASI DI BANTEN (1900-1942) - ALI, MUFTI (Al Qalam, 2012)
This paper is written to answer two main questions (1) how many were there 'the fruits' of literate movement in Banten, especially as reflected in literature written in Roman scripts (2) whether the rise of 'those fruits' is corelated with the geographical dispersion and intensive growth of the number of the alumni of so called Dutch School? To deal with these two main questions, the present writer will discuss two sub-topics: first, the degree of literacy of Banten indigenous population, and secondly, a number of accessible literatures which were published in 1900-1942, fruits' of the competency of reading and writing of literate group of Bantenese population. Historical approach applied in this study necessitate the present writer to undertake the fallowing steps: (1) heuristical, gathering relevant historical sources and data, (2) data intetpretation, and (3) historiography or historical naration. The reconstruction of those two sub-topics are solely based on the availability of primary sources, collected from National Library and National Archives of Indonesian Republic (PERPUSNAS and ANRI), both in Jakarta. The conclusion which can be taken in this study is that (first), despite of the fact that Banten is recorded as one of residences in Java with the lowest degree of literacy among its population, the product of literacy of its people is quite rich and quality. Secondly, there was a corelation between the growth of the number of alumni of the dutch school and the degree of the productiviry in literate movement. Keywords: literate movement, alumni, Dutch school, Banten